Factors Associated With Poor Outcomes in Acute Forearm Compartment Syndrome. (September 2021) - Zhang, Dafang; Janssen, Stein J.; Tarabochia, Matthew; von Keudell, Arvind; Earp, Brandon E.; Chen, Neal; Blazar, Philip
Background: There is limited literature on risk stratification of patients with acute forearm compartment syndrome. The primary objective of this study was to identify factors associated with poor outcomes in patients with acute forearm compartment syndrome.Methods: We retrospectively identified 130 patients with acute compartment syndrome of 130 forearms treated with fasciotomies from January 2000 to June 2015 at 2 Level 1 trauma centers. Poor outcome was defined as a composite variable, including: (1) death; (2) limb amputation; (3) persistent neurological deficit; and (4) contracture. Patient- and treatment-related variables were collected. Bivariate analyses were used to screen for variables associated with poor outcome, and explanatory variables with a value of P < .05 were included in our multivariable logistic regression analyses.Results: Of the 130 patients, 43 (33%) with acute forearm compartment syndrome had poor outcomes, including 5 deaths, 5 limb amputations, 21 persistent neurological deficits, and 31 contractures. Multivariable logistic regression analyses showed that elevated serum creatine kinase at presentation ( P < .05) was associated with poor outcomes in patients with acute forearm compartment syndrome. Receiver operating characteristic curve analysis showed that a serum creatine kinase cutoff of 300 U/L yields 92% sensitivity and a serum creatine kinase cutoff of 10 000 U/L yields 95% specificity for poor outcomes in acute forearm compartment syndrome.Conclusions: Elevated creatine kinase levels above 300 U/L are a useful screening test for the highest risk patients with acute forearm compartment syndrome. Levels above 10 000 U/L may play a role in informed consent and counseling regarding expectations.